Effective Stress Management and Employee Productivity in the Nigerian Public Institutions; A Study of National Galary of Arts, Abuja, Nigeria - Marcus Garvey Orji; Gloria Nankling Yakubu (Budapest International Research and Critics University, 2020)
The objective of this study was to evaluate the effect of stress management on employee productivity in the Nigerian public institutions with particular emphasis on National Gallery of Arts, Abuja. The study is a survey research and the population of the study consists of employees of the institution with sample size of 171 determined using Taro Yamane’s formula. Primary data was used through the administration of questionnaire, and the formulated hypotheses tested by regression method. The findings revealed that there is a significant impact of physical stress management on employee productivity. Furthermore, the results also revealed that there is an insignificant impact of psychological stress management on the employee productivity. Equally there is a significant impact of emotional stress management; environmental stress management and economic stress management on employee productivity. The study concluded that effective stress management can mitigate the negative factors that distressed employees which also have a negative effect on their productivity; and recommended among others that adequate stress management should be incorporated into the fabric of Nigerian public institutions to improve the health of workers and intrapersonal relationships; ergonomic factor that reduces physical stress on a worker's body should be taken into consideration to which in turn can improve productivity; in addition, equity in compensation, feeling of been in control and meaningful task in the setting may help to reduce psychological and emotional stress to improve productivity, also providing some form of financial assistance especially in times of economic distress.